Engineering the Optical Emission and Robustness of Metal‐Halide Layered Perovskites through Ligand Accommodation. Issue 13 (1st March 2021) - Dhanabalan, Balaji; Biffi, Giulia; Moliterni, Anna; Olieric, Vincent; Giannini, Cinzia; Saleh, Gabriele; Ponet, Louis; Prato, Mirko; Imran, Muhammad; Manna, Liberato; Krahne, Roman; Artyukhin, Sergey; et al.
Abstract: The unique combination of organic and inorganic layers in 2D layered perovskites offers promise for the design of a variety of materials for mechatronics, flexoelectrics, energy conversion, and lighting. However, the potential tailoring of their properties through the organic building blocks is not yet well understood. Here, different classes of organoammonium molecules are exploited to engineer the optical emission and robustness of a new set of Ruddlesden–Popper metal‐halide layered perovskites. It is shown that the type of molecule regulates the number of hydrogen bonds that it forms with the edge‐sharing [PbBr6 ] 4‐ octahedra layers, leading to strong differences in the material emission and tunability of the color coordinates, from deep‐blue to pure‐white. Also, the emission intensity strongly depends on the length of the molecules, thereby providing an additional parameter to optimize their emission efficiency. The combined experimental and computational study provides a detailed understanding of the impact of lattice distortions, compositional defects, and the anisotropic crystal structure on the emission of such layered materials. It is foreseen that this rational design can be extended to other types of organic linkers, providing a yet unexplored path to tailor the optical and mechanical properties of these materials and to unlock new functionalities. Abstract : The organic component in 2D layered perovskites can grant access to many possibilities for material design, in view of the rich variety. This work shows how the choice of the structure and chain length of organic cations can effectively guide the precise design of the emission color and efficiency of such versatile nanomaterials.